2008
DOI: 10.1002/bdrc.20125
|View full text |Cite
|
Sign up to set email alerts
|

Cell biology of embryonic migration

Abstract: Cell migration is an evolutionarily conserved mechanism that underlies the development and functioning of uni-and multicellular organisms and takes place in normal and pathogenic processes, including various events of embryogenesis, wound healing, immune response, cancer metastases, and angiogenesis. Despite the differences in the cell types that take part in different migratory events, it is believed that all of these migrations occur by similar molecular mechanisms, whose major components have been functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 230 publications
(206 reference statements)
4
91
0
Order By: Relevance
“…Directed cell migration and polarity are crucial in various biological processes, including wound healing and immune responses, as well as in pathological phenomena, such as tumor invasion and metastasis (9)(10)(11)(12). In the present study, the chemotaxis and scratch assays showed that the [Gd@ C 82 (OH) 22 ] n nanoparticle-treated LN-229 cells exhibited a significantly decreased migration ability.…”
Section: Discussionsupporting
confidence: 51%
“…Directed cell migration and polarity are crucial in various biological processes, including wound healing and immune responses, as well as in pathological phenomena, such as tumor invasion and metastasis (9)(10)(11)(12). In the present study, the chemotaxis and scratch assays showed that the [Gd@ C 82 (OH) 22 ] n nanoparticle-treated LN-229 cells exhibited a significantly decreased migration ability.…”
Section: Discussionsupporting
confidence: 51%
“…The first spatial moment is required for Z 3 (x, y, z) and in the homogeneous case Z 1 is a constant. We rewrite (3.21) in terms of the displacements between pairs as follows dZ 2 …”
Section: A2 Numerical Methodsmentioning
confidence: 99%
“…The ability of cells to migrate as a collective, either to local sites or distant parts of the body, is fundamental for tissue repair [1], development [2] and the immune response [3]. Pathologies such as cancer can arise when the regulatory mechanisms controlling movement are disrupted [4].…”
Section: Introductionmentioning
confidence: 99%
“…Both single cell and collective migration during development are spectacular examples of physiological cell motility in 3D (Aman and Piotrowski, 2010;Keller, 2005;Kurosaka and Kashina, 2008). Microtubule organization has been the subject of early electron microscopy studies in migrating myogenic cells (Jacob et al, 1978), epiblasts that acquire invasive properties due to epithelialmesenchymal transition (EMT) during gastrulation (Granholm and Baker, 1970) and cardiac cushion cells grown in collagen gels (Bernanke and Markwald, 1982).…”
Section: Microtubule Requirement In Cell Morphogenesis and Motility Imentioning
confidence: 99%